1991
DOI: 10.1136/bmj.303.6814.1357
|View full text |Cite
|
Sign up to set email alerts
|

Childhood leukaemia and poliomyelitis in relation to military encampments in England and Wales in the period of national military service, 1950-63.

Abstract: Objective-To determine if any excess of childhood leukaemia was associated with the large and increasing numbers of national military servicemen in 1949 and 1950, particularly in rural districts. This would be a further test of the hypothesis that childhood leukaemia can originate in an infection, the transmission of which is facilitated by an increased number of unaccustomed contacts in the community.Design-Rural and urban districts, aggregated by county, were ranked by proportion of servicemen, and five gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 5 publications
3
27
0
Order By: Relevance
“…A similar pattern was found with diversity of origin of adult incomers, although the association was not significant. This is consistent with the results of several of Kinlen's studies in which the relevant population mixing was necessarily attributable to adults, because it was defined in terms of employment Kinlen, 1997) or military service (Kinlen and Hudson, 1991). Similar results were, however, found in Kinlen's studies of rural new towns (Kinlen et al, 1990) and of rural areas receiving large numbers of evacuees in wartime (Kinlen and John, 1994), where the population mixing was attributable substantially or even totally to children.…”
Section: Discussionsupporting
confidence: 89%
“…A similar pattern was found with diversity of origin of adult incomers, although the association was not significant. This is consistent with the results of several of Kinlen's studies in which the relevant population mixing was necessarily attributable to adults, because it was defined in terms of employment Kinlen, 1997) or military service (Kinlen and Hudson, 1991). Similar results were, however, found in Kinlen's studies of rural new towns (Kinlen et al, 1990) and of rural areas receiving large numbers of evacuees in wartime (Kinlen and John, 1994), where the population mixing was attributable substantially or even totally to children.…”
Section: Discussionsupporting
confidence: 89%
“…The data are also consistent with Kinlen's hypothesis of population mixing (Kinlen, 1995), particularly in relation to one study which demonstrated a marked excess of leukaemia in children under 1 year of age suggesting an infection during pregnancy (Kinlen and Hudson, 1991). The differences between males and females may be indicative of an immune modulation hypothesis, with females being more susceptible to leukaemogenic events resulting from exposure to infection.…”
Section: Epidemiologysupporting
confidence: 78%
“…Although exposure to infections is not often considered as a factor in the aetiology of infant leukaemia, one of Kinlen's studies found an excess only for children under the age of 2 years and the largest excess was for infants (Kinlen and Hudson, 1991); as noted above, EUROCLUS found infants to be intrinsically involved in spatial clustering, but the MLL status of the infant cases is unknown. Thus, the present results cannot be interpreted as indicative of an infectious aetiology for infant leukaemias having MLL gene rearrangements.…”
Section: Discussionmentioning
confidence: 97%